What is an adequate standard of living during retirement? - Johannes Binswanger; Daniel Schunk (Center for Economic Studies and ifo Institute (CESifo), 2009)
Many economists and policy-makers argue that households do not save enough to maintain an adequate standard of living during retirement. However, there is no consensus on the answer to the underlying question about what this standard should be, despite the fact that it is crucial for the design of saving incentives and pension systems. We address this question with a randomized survey design, individually tailored to each respondent's financial situation, and conducted both in the U.S. and the Netherlands. Key findings include the following. Adequate levels of retirement spending exceed 80 percent of working life spending for a majority of respondents. Minimum acceptable replacement rates depend strongly on income. Households in the Netherlands are much more risk averse than U.S. households.
Keywords: D91; H55; 330; life cycle preferences; pension reform; replacement rates; retirement saving; cross-country survey studies